2019
DOI: 10.1088/1361-6544/ab0c34
|View full text |Cite
|
Sign up to set email alerts
|

Where and when orbits of chaotic systems prefer to go

Abstract: We prove that transport in the phase space of the "most strongly chaotic" dynamical systems has three different stages. Consider a finite Markov partition (coarse graining) ξ of the phase space of such a system. In the first short times interval there is a hierarchy with respect to the values of the first passage probabilities for the elements of ξ and therefore finite time predictions can be made about which element of the Markov partition trajectories will be most likely to hit first at a given moment. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In [133] it was shown that for very chaotic systems (the most uniformly hyperbolic dynamic) escape rates are indeed generally different for different holes and relations between corresponding survival probabilities can be established for all moments of time. We refer to [134] for the first rigorous results in the mathematical theory of finite time dynamics of (strongly) chaotic systems.…”
Section: Smooth Dynamical Systemsmentioning
confidence: 99%
“…In [133] it was shown that for very chaotic systems (the most uniformly hyperbolic dynamic) escape rates are indeed generally different for different holes and relations between corresponding survival probabilities can be established for all moments of time. We refer to [134] for the first rigorous results in the mathematical theory of finite time dynamics of (strongly) chaotic systems.…”
Section: Smooth Dynamical Systemsmentioning
confidence: 99%
“…A question of general interest is to explore other factors that influence the escape rate into the hole other than the length, the number of corresponding forbidden words, and the minimum period of the hole. In [2], Bolding and Bunimovich discuss finite-time dynamical properties of the shift map on a full shift with cylinders as holes. For each , they compare the values of , the number of words of length n which end with w but do not contain w as subwords in any other place.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Open dynamical systems or dynamical systems with a hole are of interest because of their dynamical properties and also their applications; see [2, 5, 7, 9]. In [16], Pianigiani and Yorke introduced such systems and also discussed the issue of the rate of the escape of orbits into the hole (known as the escape rate ).…”
Section: Introductionmentioning
confidence: 99%